Genetic signatures of long-term evolutionary history in a herbaceous, high-polyploid, clonal plant species in Central Europe - Walden, Nora; Koch, Marcus (Annals of botany, 2025)
Genetic diversity is associated with sexual reproduction and is a driver of plant adaptation and diversification. However, there are also successful but almost exclusively vegetatively reproducing species. Among them is the Eurasian herbaceous woodland species Cardamine bulbifera. Since the Last Glacial Maximum the species has expanded as an understorey woodland plant in Europe. The dodecaploid species stems from the gene pool of diploid sister species C. bipinnata and C. abchasica from the Caucasus region. We identified a genetically very diverse population in north-eastern Austria (the unglaciated Thaya Valley) lacking signatures of contemporary gene flow, in which genetic variation most likely stems from ancestral populations. We explored the hypothesis that the genetic diversity observed is a remnant of past reticulate rather than contemporary gene flow.We used genetic assignment analysis based on ddRAD data, genetic network analysis and comparisons of the nuclear and plastid gene pools to infer contemporary gene flow in the study area at Thaya Valley. Georeferenced genotypes at the Thaya Valley were assigned to woodland types and the spatial distribution of both maternally and biparentally inherited genetic variation from the plastid and nuclear genome was described.We found five specific genetic clusters for C. bulbifera with little evidence for contemporary gene flow among individuals in the Thaya Valley. Genetically admixed individuals carried a genomic signature also found in the ancestral species. These individuals were rare and likely represent also vegetatively and thereby clonally propagated old genetic variants. An eastern plastome type co-segregated with one single ddRAD genetic cluster and was found additionally in highly admixed genotypes only. Micro-scale distribution patterns of genotypes follow woodland types and ecological clines and indicate differences in the adaptive potential of identified and vegetatively dispersed plants.The studied population exhibits considerable genetic variation from past reticulate processes and provides compelling evidence for the hypothesis that past genetic variation has been preserved in this polyploid woodland species.